2019
DOI: 10.1007/s13770-019-00181-3
|View full text |Cite
|
Sign up to set email alerts
|

Histological Method to Study the Effect of Shear Stress on Cell Proliferation and Tissue Morphology in a Bioreactor

Abstract: BACKGROUND: Tissue engineering represents a promising approach for the production of bone substitutes. The use of perfusion bioreactors for the culture of bone-forming cells on a three-dimensional porous scaffold resolves mass transport limitations and provides mechanical stimuli. Despite the recent and important development of bioreactors for tissue engineering, the underlying mechanisms leading to the production of bone substitutes remain poorly understood. METHODS: In order to study cell proliferation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The samples were scanned by X-ray micro-tomography and the tridimensional arrangements of the beads and the tissue were obtained after image reconstruction. Preliminary experiments showed that tissue proliferation on glass and polyacetal bead stacks in static conditions (without flow) was negligible compared to dynamic conditions [39,40], producing too little tissue volume to be resolved by X-ray microtomography. Additionally, mass transport estimates in similar culture conditions and close flow rate indicate that oxygen and nutrient supply is in excess during most of the three weeks of culture [39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were scanned by X-ray micro-tomography and the tridimensional arrangements of the beads and the tissue were obtained after image reconstruction. Preliminary experiments showed that tissue proliferation on glass and polyacetal bead stacks in static conditions (without flow) was negligible compared to dynamic conditions [39,40], producing too little tissue volume to be resolved by X-ray microtomography. Additionally, mass transport estimates in similar culture conditions and close flow rate indicate that oxygen and nutrient supply is in excess during most of the three weeks of culture [39].…”
Section: Resultsmentioning
confidence: 99%
“…The cylindrical growth chamber (13.8 mm diameter, 5 cm high, made of polycarbonate) is randomly filled by mono disperse polyacetal beads (2 mm diameter). Let us note that bead-based scaffolds have been identified as good candidates for tissue engineering and therefore have been investigated multiple times [4,32,39,40,[44][45][46][47]. The beads are immobilized by two polycarbonate grids (0.5 cm high), inserted in the growth chamber at the bioreactor inlet and outlet.…”
Section: Perfusion Bioreactormentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of multi‐layered structure require 3‐D environments (at the cell scale). Such sites actually exist in stackings of beads: they are typically located at the contact point between beads . On the contrary, stackings of cubes seem to have fewer sites able to induce 3‐D (multi‐layered) proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Methodology combining histological procedure and image analysis allows the description and quantification of cell proliferation within bioreactor. 53 However, this method can only generate a crude rather than comprehensive depiction of the 3D scaffold, primarily because its destructive nature leads to an incomplete representation of the 3D tissue. Over the last 10 years, nondestructive three-dimensional image-based technology has made steady progress (i.e., the ability to visualize micrometric objects).…”
Section: Discussionmentioning
confidence: 99%